Baseline 101 – who is who? - Marlin, Nadine; Allotey, John (BJOG : an international journal of obstetrics and gynaecology, 2019)
Baseline tables show the characteristics of research subjects included in a study. Depending on the study design they may have specific purposes but generally they show if the population included conforms to the eligibility criteria of the study. They also indicate what population the results could be generalised to.